Public preferences towards naturalistic and designed landscape pattern in park area / Noralizawati Mohamed - Mohamed, Noralizawati (2009)
Landscape preference research has been widely discusse d in the fields of landscape architecture and environmental psychology. A forum on urban and park as natural resources, held at IFLA World Congress 2007 concluded that urban people are becoming more aware and concerned about the quality of urban parks and urban forest parks. In previous research findings, it was noted that the public was influenced and responded differently towards different types of landscape patterns in both types of park areas due to many reasons. Previous researches depict that the nat uralistic landscape pattern in urban forest parks are preferred by people because it may provide benefits in terms of ecology and psychology. However, a certain number of researches found that some people preferred urban forest parks lesser due to the landscape pattern of the area which might contribute to a frightening or unsafe feeling and that it appears disorganised. It was found that the public are more comfortable with a neat, formal and tidy approach in designed landscape patterns in urban park areas. Therefore, the purpose of this research is to investigate the public preferences towards the naturalistic and designed landscape patterns. The publics’ preferences towards these landscape patterns are investigated using a questionnaire survey that is divided into 3 sections. Section A deals with questions on the demographi c background of the respondents, Section B deals with questions on preferences towards photographs using the Likert scale and Section C consists of open -ended questions. The results revealed that the public preferred both types of landscape patterns with a mean value at 3.27 for the naturalistic approach (Canopy Walkway Trail) and 3.22 for the designed approach (Metropolitan Park). Even though the statistical means depict slight differences, this research found that there are still significant differences between the publics’ preferences to the landscape patterns based on the photographs that were rated by the respondents. It confirmed that in naturalistic landscape patterns, the responde nts preferred the natural elements and natural arrangement scenes while in the designed landscape pattern, they preferred the facilities elements and formal arrangement scenes. It is hoped that the preferred scenes by the respondents can be maintained and the ones not preferred be improved upon in future.